MODERATISME TAFSIR HUSEIN FADLULLAH TERHADAP INKLUSIVITAS PENAFSIRAN AYAT-AYAT JIHAD - Agus Mughni Muttaqin; Abdullah Abdul Kadir (MUMTAZ : Jurnal Pendidikan Agama Islam, 2023)
The purpose of this study is to examine and build the construction of moderation in Fadhlullah's interpretation. In addition, more specifically, this discussion will also examine the implications of the application of moderation in Fadhlullah's interpretation of the verses of jihad in the Qur'an. This research uses a qualitative approach, with thematic (mawÃƒÂ¡Ã‚Â¸Ã‚ÂÃƒâ€¦Ã‚Â«'ÃƒÆ’Ã‚Â®), descriptive-analytical and library research methods. The approach method uses Philosophical-Constructionist, and Sociology-Historical. The results of this study are: The construct of moderation in Fadhlullah's interpretation consists of al-manÃƒÂ¡Ã‚Â¸Ã‚Â¥aj al-ÃƒÂ¡Ã‚Â¸Ã‚Â¥arakÃƒâ€žÃ‚Â«, which is moderate (wasaÃƒÂ¡Ã‚Â¹Ã‚ÂÃƒâ€žÃ‚Â«). The manÃƒÂ¡Ã‚Â¸Ã‚Â¥aj rests on three main constructions; First, discipline in the semantic literal meaning; Second, a proportional understanding of the context of the Qur'anic verse, either when it was revealed or interpreted; Third, inclusiveness in understanding and applying the ÃƒÂ¡Ã‚ÂºÃ¢â‚¬Å“Ãƒâ€žÃ‚ÂÃƒÂ¡Ã‚Â¸Ã‚Â¥ir and inner meaning of the Qur'an. In terms of its implications for the verse of jihad, Fadhlullah has a balanced paradigm of thought; jihad is not only aimed at obedience and the value of worship alone, or only has a dimension for human kindness, but both aspects are the basis of his paradigm of thought.